Case Studies in Food Policy for Developing Countries : Domestic Policies for Markets, Production, and Environment - Cheng, Fuzhi; Pinstrup-Andersen, Per (Book collections on Project MUSE., 2009)
Volume II of the Case Studies addresses the issues of domestic policies for markets, production, and the environment.